O-007 Colitis Vaccine: Flagellin-Elicited Immunity Keeps Motile Bacteria in Check and Protects Against Intestinal Inflammation. (March 2016) - Chassaing, Benoit; Tran, Hao; Gewirtz, Andrew
Abstract : Background: Inflammatory Bowel Disease (IBD) is driven by a breakdown in the normally mutually beneficial host-microbiota relationship. Manipulating the host portion of this relationship, particularly antagonizing immune-promoting cytokines, has improved IBD management. We recently reported that disturbance of the intestinal microbiota using 3 different approaches (infectious agent, genetic predisposition and environmental factor) leads to a microbiota with increased pro-inflammatory potential and development of intestinal inflammation. Approaches to impact the microbiota to ameliorate IBD are not well developed despite the appreciation that microbiota composition has a great impact on disease outcome. Hence, we hypothesize that manipulating the microbiota so as to make it inherently less pro-inflammatory (i.e., reduce levels of innate immune activators) may ultimately provide a novel approach to prevent and/or treat chronic intestinal inflammation. Methods: Mice were treated with either PBS or purified flagellin (10 μg) weekly by intraperitoneal injection. Feces were collected weekly and used for downstream analysis: fecal flagellin and LPS via cell-based reporter assay, inflammatory marker lipocalin-2, fecal and serum anti-flagellin IgA and IgG via ELISA, and microbiota composition via 16S RNA Illumina Miseq sequencing. Twelve weeks following initial the treatment, mice were either euthanized and intestinal samples processed to measure the intestinal inflammatory state (histopathology via hematoxylin & eosin staining, myeloperoxidase enzymatic activity, bacterial localization via confocal microscopy), or subjected to anti-IL-10 receptor treatment before tissue collection. Results: Weekly treatment of mice with flagellin led to a strong induction of serum anti-flagellin IgG and fecal anti-flagellin IgA. Moreover, such immunization against bacterial flagellin was associated with strong modification of fecal microbiota composition that associated with a decrease in pro-inflammatory potential, as revealed by the decrease in level of fecal bioactive flagellin. Such flagellin immunization and microbiota composition alteration protected mice against intestinal inflammation induced by anti-IL-10 receptor antibody treatment, as revealed by decreased spleen weight as well as decrease colon weight/length ratio in immunized animals compared to PBS-treated group. Conclusions: Flagellin inoculation alters microbiota composition and decreases level of fecal flagellin, and associated with protection against intestinal inflammation development. The mucosal immune system holds the power to reshape the microbiota and protect against inflammatory bowel disease.